Modeling Highly Buoyant Flows in the Castel Giorgio: Torre Alfina Deep Geothermal Reservoir - De Caro, Mattia; Fisher, Thomas; Colucci, Francesca; Magri, Fabien; Volpi, Giorgio; Crosta, Giovanni B. (Geofluids, 2018)
The Castel Giorgio-Torre Alfina (CG-TA, central Italy) is a geothermal reservoir whose fluids are hosted in a carbonate formation at temperatures ranging between 120°C and 210°C. Data from deep wells suggest the existence of convective flow. We present the 3D numerical model of the CG-TA to simulate the undisturbed natural geothermal field and investigate the impacts of the exploitation process. The open source finite-element code OpenGeoSys is applied to solve the coupled systems of partial differential equations. The commercial software FEFLOW® is also used as additional numerical constraint. Calculated pressure and temperature have been calibrated against data from geothermal wells. The flow field displays multicellular convective patterns that cover the entire geothermal reservoir. The resulting thermal plumes protrude vertically over 3 km at Darcy velocity of about 7⁎10-8 m/s. The analysis of the exploitation process demonstrated the sustainability of a geothermal doublet for the development of a 5 MW pilot plant. The buoyant circulation within the geothermal system allows the reservoir to sustain a 50-year production at a flow rate of 1050 t/h. The distance of 2 km, between the production and reinjection wells, is sufficient to prevent any thermal breakthrough within the estimated operational lifetime. OGS and FELFOW results are qualitatively very similar with differences in peak velocities and temperatures. The case study provides valuable guidelines for future exploitation of the CG-TA deep geothermal reservoir.